The Language of Classification in Accounting Texts in the Framework of SFL - Bahtera Sembiring (Jurnal Bahasa Inggris Terapan, 2018)
This paper reports the study of language of classification on accounting texts using the Systemic Functional Linguistics (SFL) framework. It focuses on how language of classification is realized structurally on a such text. The studies conducted by Wignell, Martin and Eggins (1993) focusing on physical geography texts and Khorina, Suyatna and Indira (2017) concerning with electronics engineering texts, identified that classification was realized either by intensive or possessive relational process clauses working on attribute mode. In relation to the prior studies, the data were collected from two accounting textbooks used as references by the students of Accounting Department at PoliteknikNegeri Bandung (Polban). Both of the types of relational process clauses were found in the texts consisting of 14 clauses classified as intensive and 17 belonging to possessive ones. Both types of the clauses contain attributive relational process. The attributive relational process occuring in intensive relational process clauses is realized solely by verb be. However, the relational process which appears in possessive relational process is realized by several verbs which are break, classify, consist, divide, and include. The implication of this study is not only for modelling English grammar of Accounting texts, but also for translation study.Key words: SFL, classification, intensive relational process clause, possessive relational process clause